Representation and participation in management committees of teaching and service integration - Carine Vendruscolo; Marta Lenise do Prado; Maria Elisabeth Kleba; Izabella Barison Matos (Universidad de Antioquia, 2016)
Objective. To analyze the representation and participation of the management, attention, teaching and social control segments in management committees of health teaching-service integration. Methods. Qualitative research with exploratory-analytical approach that involved representatives of these segments who participate in the management instances of the Pro-Health integrated proposal of Chapecó, Santa Catarina, Brazil. The data was collected through semi-structured interviews with 11 members of the segments and observation of six meetings of instances between October 2012 and April 2013. Results. The following categories emerged: Representation through dialogue: possibility to negotiate; Legitimacy of representation: establishing fecund relationships; Disparity in the representation of the segments: the four-way approach in disharmony. Conclusion. It is incipient participation of some segments; there are different understandings as to the perception of the meaning of representation. There are conflicts, but the dialogue prevails, provided that the subjects need improve their communication skills.   How to cite this article: Vendruscolo C, Prado ML, Kleba, ME, Matos, IB. Representation and participation in management committees of teaching and service integration. Invest. Educ. Enferm. 2016; 34(3): 474-482